Multi-Omics Integration in Clinical Chemistry: A New Frontier in Early Disease Detection - Hamza, Sajjad Sami Farhan; Ali, Nabaa Hussein kareem; Darwish, Sharmeen Khider Salim; ubid, Abbas Fadhil khazaal; Hawas, Qasim Sabbar Aadi (American Journal of Biomedicine and Pharmacy, 2025)
The field of clinical chemistry is undergoing a profound transformation as technological advances accelerate the convergence of disciplines for comprehensive characterization of biological systems and molecules. Integrating traditional clinical chemistry with omics technologies is emerging as a powerful new approach for capturing the complexity of biological systems far beyond established strategies. The combination of omics and clinical chemistry offers the potential for a more comprehensive and far-reaching understanding of health and illness that has the potential to change the paradigm of early-disease detection for the twenty-first century Integration of omics and clinical chemistry is unfolding in the context of what has been termed multi-omics, where multiple omics technologies are combined and applied simultaneously to the same research, clinical, or laboratory problem.